Penilaian Formatif Berbasis Karakter Saat Pembelajaran Daring DI MI Miftahul Akhlaqiyah Bringin Semarang - Luq Yana Chaerunnisa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The purpose of this study was to find out character-based formative assessments during online learning during the Covid-19 pandemic at MI Miftahul Akhlaqiyah Bringin Semarang. The researcher used a qualitative descriptive approach. The subject used was the 5th grade teacher at MI Miftahul Akhlaqiyah Bringin Semarang. The results showed that: 1) formative assessment planning using whatsapp features including whatsapp group and videocall 2) Formative assessment was carried out at the end of each learning material as an assignment as well as activity assessment through question and answer interaction using videocall, 3) character-based formative assessment was carried out through communication to parents to be able to participate in directing students and taxonomy characterization. 4) Obstacles faced by teachers are limited device storage, cellphones that have to take turns with parents slowing the assessment process, late collection of assignments.